2001
DOI: 10.2105/ajph.91.10.1679
|View full text |Cite
|
Sign up to set email alerts
|

Partner Violence Among Adolescents in Opposite-Sex Romantic Relationships: Findings From the National Longitudinal Study of Adolescent Health

Abstract: Psychological and minor physical violence victimization is common in opposite-sex romantic relationships during adolescence. The sex-specific associations between sociodemographic characteristics and patterns of partner violence victimization underscore the importance of pursuing longitudinal, theory-driven investigations of the characteristics and developmental histories of both partners in a couple to advance understanding of this public health problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
305
8
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(354 citation statements)
references
References 34 publications
29
305
8
8
Order By: Relevance
“…Even though adolescent IPV affects both sexes, there are marked gendered differences between young women's and young men's experiences and risks related to IPV: Adolescent girls are more at risk of experiencing sexual violence than boys are (Halpern, 2001), and, in general, of becoming victims of dating aggression (Oleary et al, 2008), engaging in physical force in self-defense, and being seriously injured (Hickman et al, 2004;Davis, 2008;Silverman, Raj et al, 2001). They are also more likely to be killed by a partner than are males.…”
Section: Gender Normsmentioning
confidence: 99%
“…Even though adolescent IPV affects both sexes, there are marked gendered differences between young women's and young men's experiences and risks related to IPV: Adolescent girls are more at risk of experiencing sexual violence than boys are (Halpern, 2001), and, in general, of becoming victims of dating aggression (Oleary et al, 2008), engaging in physical force in self-defense, and being seriously injured (Hickman et al, 2004;Davis, 2008;Silverman, Raj et al, 2001). They are also more likely to be killed by a partner than are males.…”
Section: Gender Normsmentioning
confidence: 99%
“…Girls and younger women experience the highest per capita rates of physical and sexual violence from dating partners. [5][6][7][8] Like IPV, TDV victimization is associated with multiple negative physical, sexual, and psychological health outcomes. [9][10][11] Investigations among youth are critical to inform efforts to prevent such violence from becoming a pattern of behavior within intimate relationships into adulthood-and to reduce early victimization and related health, social, and behavioral effects of such violence across the life course.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Those experiencing IPV may present to healthcare services with physical injury, [3] depression, or suicidal ideation and suicide attempts. [4] Studies worldwide have shown that physical, psychological and sexual violence vary widely across countries and have been reported in 10 -50% of relationships for individuals aged up to 19 years, including in the USA, India, Nigeria, China, [5] the UK, [6,7] Tanzania [8] and South Africa (SA). [5,8,9] Most studies have reported that psychological violence is most common, followed by physical violence and then sexual violence.…”
mentioning
confidence: 99%
“…[4] Studies worldwide have shown that physical, psychological and sexual violence vary widely across countries and have been reported in 10 -50% of relationships for individuals aged up to 19 years, including in the USA, India, Nigeria, China, [5] the UK, [6,7] Tanzania [8] and South Africa (SA). [5,8,9] Most studies have reported that psychological violence is most common, followed by physical violence and then sexual violence. [10,11] Risk factors for perpetration and victimisation of IPV in adolescent relationships also vary between countries, and associations with higher age, [12] not being raised by a biological mother, [11] higher maternal education, [8] substance use, particularly alcohol, [9,11,13] previous maltreatment, violence in the home and aggressive peer networks, [10] especially at school, [13] and attitudes supportive of male superiority, [6,9] and for girls having an older partner, [8,10] have been reported.…”
mentioning
confidence: 99%